ASTHMA CAUSED BY THE GRAIN WEEVIL. Issue 2 (April 1965) - Frankland, A. W.; Lunn, J. A.
Abstract : The grain weevil ( Sitophilus granarius ) caused symptoms of allergic rhinitis and asthma in two laboratory workers, one after exposure to weevil dust for only six months and the other after three years. The former worker also noticed sneezing when she was cooking with National Flour. Skin testing with extracts of the grain weevil faecal dust gave positive skin responses. The antibodies were successfully transferred by passive sensitization using the Prausnitz-Kustner technique. One hundred patients attending an allergy clinic for seasonal hay fever symptoms were also tested. All reacted to skin testing to a high dilution of grass pollens, and 51 gave some response to extracts of Sitophilus granarius ; in 18 the wheal size was at least 6 mm. in diameter. The significance of the positive responses in these 18 patients is at present unexplained. One of the laboratory workers was so sensitive to weevil dust that she had to leave the laboratory; the other worker, by using an extractor fan and wearing a mask, could remain free of symptoms. Sitophilus granarius, like other insects, easily gives rise to inhalant allergic symptoms and may be a possible cause of baker's asthma which has not been previously considered.